Factors of Interest in Choosing A Profession of Students of The Graduating Class of General Secondary Education Schools - Yetmisheva Dilorom G‘ulomovna (Web of Journals Publishing, 2023)
This article explores the factors that influence the caree choices of students in the graduating class of general secondary education schools. The transition from secondary education to higher education or the workforce is a crucial juncture in a young person's life, and the choices made during this period can significantly impact their future. Understanding the factors that drive these decisions is essential for educators, policymakers, and career counselors to provide effective guidance and support to students. Through a comprehensive analysis of various factors, including personal interests, family influence, societal expectations, and economic considerations, this study aims to shed light on the complex decision-making process of students as they embark on their professional journeys.
Keywords: Career choices; Graduating students; General secondary education; Influencing factors; Decision-making process.